Tracking System for Indoor TV Antenna Based on CVBS Signal Processing - Herti Miawarni; M. Mahaputra Hidayat; Surya Sumpeno; Eko Setijadi (National Research and Innovation Agency, 2017)
Analog terrestrial TV is still a popular choice for urban societies although the migration to digital system has already begun. Video quality of analog TV was heavily influenced by performance of the antenna. Most users prefer to use indoor antenna due to its simplicity. The disadvantage of this type of antenna is the users may need to change the antenna direction repeatedly when they change to different TV channel. In this research, we designed and developed tracking system that enable indoor TV antenna to adjust its direction automatically to get optimum video clarity. This system is built by several servo motors and telescopic antennas. Composite Video Baseband Signal (CVBS) processing is used to obtain reference information regarding video clarity level conditions on TV screen. The results show that CVBS signal processing has performance in describing video clarity level. System performance has been verified from trial results on some UHF channels. Minimum tracking time is reach 23.4 second and the maximum reach 24.6 second.